EDUCATIONAL DIGITAL COMIC ABOUT BODY POSITIVITY FOR TEENAGERS 15 TO 18 YEARS OLD - Chalisha, Moira Najla; Aditya, Dimas Krisna; Bastari, Rendy Pandita (eProceedings of Art & Design, 2024)
Adolescence is a developmental phase characterized by significant biological, psychological, cognitive, and social changes, often accompanied by decreased selfconfidence and increased vulnerability to body image issues. Negative body image is common among teenagers, with girls often struggling with societal pressures to conform to thin ideals, and boys facing pressures to achieve muscular physiques. Despite the growing awareness of body positivity, many teens still misunderstand it, seeing it only as self-acceptance rather than a broader movement for inclusivity and respect for all body types. This research focuses on creating digital comic media to educate teenagers, aged 15-18, about the true meaning of body positivity through Instagram. The aim is to improve their understanding and acceptance of diverse body types, addressing misconceptions and promoting healthier self-perceptions. To mitigate the risks the lack of not knowing the meaning of body positivity, it is essential to provide resources and educational materials on how to practice body positivity effectively. The proposed Digital Comic aims to empower young individuals to embrace self-acceptance and confidence without succumbing to harmful positivity. Keywords : body positivity, self-acceptance, digital comic